Batas Antara Manusia dan Replika Dalam Film Blade Runner 2049: Kajian Posthumanisme - Reza Rizkia (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This study aims to analyze how the boundaries between humans and replicants are represented in the film Blade Runner 2049, using Rosi Braidotti’s posthumanism theory, supplemented by the ideas of Donna Haraway and N. Katherine Hayles. The study employs qualitative methods, with a descriptive approach involving an analysis of dialogue, scenes, and visual elements in the film. Data was collected from the film as the primary source, along with books and academic articles as secondary sources. The results show that the film presents the boundary between humans and replicants as something dynamic, rather than a rigid separation. This is demonstrated through the replicants’ ability to develop identities, express emotions, establish social relationships, and make moral decisions. Thus, Blade Runner 2049 not only questions what it means to be human, but also explores broader themes related to human nature.It’s a construct of humanistic thought that places humans at the center and as the primary measure of life. It is hoped that this research will contribute to the study of literature and film, particularly in the development of posthumanist approaches to analyzing works of science fiction.